Supply Chain Disruption, Resilience Capability, and Firm Survival in Medan's Palm Oil Industry Post-COVID-19 - Dayat Firman; Komar Yusuf; Attariq Khuda (Journal of Economics Business Industry, 2024)
This study aims to examine the impact of supply chain disruption on firm survival in the palm oil industry in Medan following the COVID-19 pandemic. It also investigates the mediating role of resilience capability in mitigating the negative effects of disruptions on organizational sustainability. This research employs a mixed-methods approach using a sequential explanatory design. Quantitative data were collected from 196 palm oil companies in Medan and surrounding areas through structured questionnaires. The data were analyzed using structural equation modeling (SEM) to assess the relationships between variables. Additionally, qualitative insights were used to enrich the interpretation of the findings. Resilience capability was measured through four dimensions: adaptability, agility, robustness, and collaborative networking. The results indicate that supply chain disruption has a significant negative effect on firm survival. However, resilience capability plays a crucial mediating role in reducing this negative impact. Firms with higher levels of resilience are better able to maintain operational performance despite severe disruptions. Furthermore, factors such as technology adoption and firm size also influence a company’s ability to survive during crisis conditions. This study contributes to the supply chain management literature by integrating supply chain disruption and firm survival within the context of the palm oil industry in a developing country. It highlights the strategic importance of resilience capability as a mediating mechanism and provides empirical evidence from the post-pandemic period, offering practical implications for building more adaptive and resilient supply chains.